Antioxidant activity and upregulation of antioxidant enzymes of phenolic glycosides from Aquilaria crassna leaves - Chonlakan Supasuteekul (2018)
The leaves of Aquilaria crassna Pierre ex Lecomte (Thymelaeaceae) have been used in the traditional medicine and consumed as a health-promoting tea in several Asian countries. This study investigated the antioxidant activity of three major bioactive constituents of A. crassna leaves, genkwanin 5-O-β- primeveroside (1), iriflophenone 3,5-C-β-D-diglucoside (2) and iriflophenone 3-C-β-D-glucoside (3) using DPPH and superoxide scavenging assays, as well as their effects on induction of mRNA and protein expressions of antioxidant enzymes in HEK-293 cells. The benzophenone glycoside 3 exhibited significant scavenging activity against both types of free radicals and increased the mRNA expression of antioxidant enzymes such as glutathione peroxidase-1, glutathione reductase and heme oxygenase-1 in HEK-293 cells. In addition, all three compounds also increased the protein expression of glutathione peroxidase-1. These findings revealed the effects of these compounds at cellular level, and might be useful for the development of A. crassna leaves as supplements for prevention of oxidative stress.